The Effect of Promotion and Quality of ADAMIX Instant Cement on Increasing Sales - Yusuf, Muhammad; Suwarda, Hendra; Khasanah, Siti Uswatun (INNOVATION RESEARCH JOURNAL, 2025)
This study aims to determine the effect of promotion and product quality on increasing sales of Adamix Instant Cement products at PT Adamix Mortar Indonesia, both partially and simultaneously. The method used in this study is a quantitative method with an associative approach. The sample in this study were all 30 employees of the promotion and production division. The data analysis techniques used were multiple linear regression, t-test, F-test, and coefficient of determination (R²) test. The results showed that partially, the promotion variable (X₁) had a positive and significant effect on increasing sales, with a significance value of 0.006 <0.05. Product quality (X₂) also had a positive and significant effect with a significance value of 0.032 <0.05. Simultaneously, promotion and product quality had a significant effect on increasing sales, as evidenced by the calculated F value of 11.514 > F table 1.701 and a significance value of 0.006 <0.05. The coefficient of determination (R²) of 46% indicates that the variation in sales increases can be explained by promotional variables and product quality, while the remaining 54% is influenced by other factors not examined. The results of this study emphasize the importance of effective promotional strategies and improving product quality in driving sales,